Web application vulnerabilities : detect, exploit, prevent - Cross, Michael, 1965- (Syngress Pub., 2007)
"In this book, we aim to describe how to make a computer bend to your will by finding and exploiting vulnerabilities specifically in Web applications. We will describe common security issues in Web applications, tell you how to find them, describe how to exploit them, and then tell you how to fix them. We will also cover how and why some hackers (the bad guys) will try to exploit these vulnerabilities to achieve their own end. We will also try to explain how to detect if hackers are actively trying to exploit vulnerabilities in your own Web applications."--Jacket